2024
DOI: 10.1186/s12885-024-11842-5
|View full text |Cite
|
Sign up to set email alerts
|

NUSAP1 promotes pancreatic ductal adenocarcinoma progression by drives the epithelial-mesenchymal transition and reduces AMPK phosphorylation

Yuan Liu,
Rong Tang,
Qing-Cai Meng
et al.

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis, and its molecular mechanisms are unclear. Nucleolar and spindle-associated protein 1 (NUSAP1), an indispensable mitotic regulator, has been reported to be involved in the development of several types of tumors. The biological function and molecular mechanism of NUSAP1 in PDAC remain controversial. This study explored the effects and mechanism of NUSAP1 in PDAC. Methods Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In studies conducted on pancreatic cancer cells, BUB1 was identified as a promoter of cell proliferation, migration and gemcitabine resistance [24]. Both ASPM and BUB1 interact with UBE2C, KIF23, KIF2C, KIF11, NUF2, CDK1, BUB1B and NUSAP1, each of which has previously been associated with the initiation and/or progression of PAAD [25][26][27][28][29][30][31][32]. The results of our functional enrichment analysis suggest that SKA3 is correlated with genes that promote proliferation, as well as those responsible for ensuring the high fidelity of chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted on pancreatic cancer cells, BUB1 was identified as a promoter of cell proliferation, migration and gemcitabine resistance [24]. Both ASPM and BUB1 interact with UBE2C, KIF23, KIF2C, KIF11, NUF2, CDK1, BUB1B and NUSAP1, each of which has previously been associated with the initiation and/or progression of PAAD [25][26][27][28][29][30][31][32]. The results of our functional enrichment analysis suggest that SKA3 is correlated with genes that promote proliferation, as well as those responsible for ensuring the high fidelity of chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
“…NUSAP1 serves as a pivotal oncogenic factor in pancreatic ductal adenocarcinoma, driving proliferation, migration, and epithelial-mesenchymal transition, while inhibiting the AMPK signaling pathway. Elevated NUSAP1 expression is associated with unfavorable prognosis ( Liu et al, 2024 ). Furthermore, heightened expression of TPX2 in HCC promotes cell proliferation and invasion through AKT signaling activation and upregulation of MMP2/9, underscoring its potential as a therapeutic target for hepatocellular carcinoma ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%